INTERPLAY BETWEEN BUSINESS EDUCATION AND SUSTAINABLE ECONOMIC DEVELOPMENT: EVIDENCE FROM DIGITAL SKILLS POSSESSED BY BUSINESS EDUCATION GRADUATES (NAU Journal of Technology and Vocational Education, 2024)
Acquisition of digital skills among graduates has become crucial to enable them to contribute sustainably for economic development. The study determined the interplay between business education and sustainable economic development through digital skills possessed by business education graduates. Two research questions and two null hypotheses guided the study. The study adopted survey research design, and 109 postgraduate students in Anambra State were studied without sampling. A-20 item questionnaire validated by three experts in the field of education was used for data collected. The reliability of the instrument was established using Cronbach’s alpha formula which yielded coefficients of 0.91 and 0.78 obtained for e-entrepreneurial skills and cyber security skills respectively.  Mean, standard deviation and t-test were used for data analysis. Findings showed that the level business education graduates possess e-entrepreneurship and cybersecurity skills necessary for contributing to sustainable economic development is low. Gender difference was not found in their mean ratings on the level of e-entrepreneurship and cybersecurity skills possessed for sustainable economic development. It was recommended that curriculum of business education programme should be reviewed so as to incorporate cybersecurity contents.